Exploring factors influencing teachers’ self-efficacy at rural schools during the Covid-19 pandemic - Nomthandazo Tshabalala (International Journal of Studies in Psychology)
The worldwide COVID-19 pandemic greatly affected our normal life. People had to adapt to new living styles to prevent the spread of disease. COVID-19 created enormous challenges and changes in educational systems. Teachers at work faced many challenges, increasing their stress levels and forcing them into early retirement. Some teachers remained positive, committed, and inspired by the challenges. These factors influenced teachers to work hard and believe they could overcome obstacles. This study explored factors influencing teachers’ self-efficacy at rural schools during the COVID-19 pandemic. It employed a qualitative approach and interpretive paradigm. It used the phenomenological research design. This study found various factors influenced teachers’ self-efficacy during the COVID-19 pandemic such as technology, electricity, and overcrowded classrooms. It concludes that teachers remain positive, committed, and inspired by the challenges.